Common European framework of reference for languages (CEFR): insights into global policy borrowing in Malaysian higher education. (27th May 2019) - Ahmad Afip, Liyana; Hamid, M. Obaidul; Renshaw, Peter
ABSTRACT: The Common European Framework of Reference for Languages (CEFR) has emerged as a global policy in language education which has been 'borrowed' by nations across the world. This paper presents a critical analysis of Malaysia's borrowing of the CEFR as part of English language curriculum reform with particular reference to policy motivation and implementation processes as outlined in the English Language Education Roadmap for Malaysia (2015–2025). The analysis draws on Phillips and Ochs's (2003, "Processes of Policy Borrowing in Education: Some Explanatory and Analytical Devices." Comparative Education 39 (4): 451–461.) framework for examining educational policy borrowing to highlight challenges as well as prospects of the implementation of the global policy in higher education in Malaysia.